Social Support as a Buffer of the Association between Sexual Assault and Trauma Symptoms Among Transgender and Gender Diverse Individuals - Grocott, Lauren R. (Journal of interpersonal violence, 2023)
The prevalence of experiencing sexual assault is alarmingly high among Transgender and Gender Diverse people (TGD; people whose gender identities and/or expressions are not traditionally associated with their sex assigned at birth) and is associated with various mental health sequalae. Perceived social support has been shown to abate the negative outcomes of sexual assault among cisgender individuals, yet little is known about this association among TGD people, especially which provider of support (i.e., family, friends, or significant others) may be most beneficial. To that end, 191 TGD adults were recruited through Amazon’s Mechanical Turk to examine perceived social support as a potential moderator of the association between sexual assault victimization and post-sexual assault trauma symptomology. Results showed an interaction trending toward significance between sexual assault and support from a significant other. Decomposition of this interaction demonstrated that sexual assault was associated with post-assault trauma symptoms when support from a significant other was low (ß = .25, p < .05) but not high (ß = .10, p = .089). The interaction between sexual assault and perceived social support was not significant for perceived support from friends (p = .133) or family (p = .954). Findings highlight the need for additional research on perceived social support as a potential buffering mechanism between sexual assault and post-assault symptomology in TGD people.